PERAN MASYARAKAT LOKAL DALAM PENGEMBANGAN GEOSITE GEOPARK KALDERA TOBA SILAHISABUNGAN MENUJU GEOPARK GLOBAL UNESCO - Karmel Simatupang; Roberto Roy Purba (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
This study aims to determine to which extent local communities are involved and play a role in the development of Toba Caldera Geopark (TCG) in the Silahisabungan geosite, Silahisabungan Sub-district, Dairi Regency, North Sumatra Province. The research method was conducted with a descriptive qualitative approach, by conducting literature studies, and field observations. The researcher acts as a participant-observer. This study found that the local communities of Silahisabungan generally did not understand about geopark, and its role in the development of Silabisabungan TCG geosite. This was mainly due to the lack of public knowledge about geopark and geosite. On the other hand the government is still reluctant to commit to allocate budgets in order to empower local communities. As TCG proposes to UNESCO Global Geopark, the Silahisabungan geosite has the potential in terms of geological, cultural and biological diversity that can be seeded. Therefore, the government and other parties concerned, it is very important to fully support the development of Silahisabungan geosite. Local communities should receive assistance and counseling on how to maximize the potential of their region with the principles of sustainable tourism.